Variations in elemental and isotopic compositions of Cu, Zn, and Cd in mushrooms: are they site- or species-dependent? - Alexandre V. Andronikov; Irina E. Andronikova; Eva Martinkova; Ondrej Sebek; Anna Vynnychuk; Marketa Stepanova (Fungal Biology, 2026)

Source apportionment of reactive nitrogen in fog vs. rain using isotope ratios and Bayesian modeling (Ore and Eagle Mts., Central Europe) - Martin Novak; Frantisek Buzek; Bohuslava Cejkova; Daniel Hladky; Radim Seibert; Iva Hůnová; Blanka Krejci; Zdenka Chromcova; Jakub Hruška; Marketa Stepanova; Ivana Jackova; Jerzy Cabala; et al. (Journal of Hazardous Materials, 2026)

The wild-grown Boletus edulis (penny bun) mushroom from the granite-based substrate: Trace elements uptake and Mg, Cu, Zn, and Cd isotope fractionations - Alexandre V. Andronikov; Irina E. Andronikova; Eva Martinkova; Ondrej Sebek; Marketa Stepanova (Fungal Biology, 2025)

Changing isotope compositions of Mg, Ca and Sr in bulk crystalline rocks toward the weathering front: Disentangling inputs of geogenic base cations into ecosystems - Martin Novak; Yulia V. Erban Kochergina; Chris Holmden; Alexandre V. Andronikov; Vaclav Kachlik; Jana Kotkova; Irina E. Andronikova; James W. Kirchner; Jakub Hruška; Frantisek Veselovsky; Frantisek Laufek; Ondrej Pour; et al. (Applied Geochemistry, 2025)

Lead sources for aerosol in urban Upper Silesia determined from Pb isotope ratios of nine mixing end-members and Bayesian modeling - Martin Novak; Eva Martinkova; Ladislav Strnad; Radim Seibert; Daniel Hladky; Blanka Krejci; Vladislav Chrastny; Pavel Machalek; Tomas Magna; Jerzy Cabala; Ondrej Sebek; Marketa Stepanova; et al. (Journal of Hazardous Materials, 2025)

Changes in Mg-Cu-Zn isotopic features in a system red cracking bolete – soil over an extended period - Alexandre V. Andronikov; Irina E. Andronikova; Ondrej Sebek; Eva Martinkova; Marketa Stepanova (Applied Geochemistry, 2025)

Ammonium and nitrate in ice accretions and snow at two Central European montane locations: δ15N and δ18 O H 2 O isotope ratios, fluxes and sources - Martin Novak; Frantisek Buzek; Radim Seibert; Iva Hunova; Daniel Hladky; Jakub Hruška; Marketa Stepanova; Bohuslava Cejkova; Jan Curik; Frantisek Veselovsky; Lenka Buresova; Eva Prechova; et al. (Science of The Total Environment, 2025)

Effect of Compositionally Different Substrates on Elemental Properties of Bay Bolete Mushrooms: Case Study of 34 Essential and Non-essential Elements from Six Areas Affected Differently by Industrial Pollution - Alexandre V. Andronikov; Irina E. Andronikova; Ondrej Sebek; Eva Martinkova; Marketa Stepanova; Oksana Perehon (Biological Trace Element Research, 2024)
We studied concentrations of 34 essential and non-essential elements in samples of edible Bay Bolete ( Imleria badia ) mushrooms added by samples of the growing substrate and bioavailable fraction. The samples were collected from six forested sites affected differently by industrial pollution and underlain by compositionally contrasting bedrock: granite, amphibolite, and peridotite. In all cases, mushrooms behaved as a bioconcentrating system for elements such as Ag, K, P, Rb, S, and Se (BCF > 1) being a bioexcluding system for the rest of the elements analyzed (BCF < 1). Most analyzed elements displayed moderate to high within-mushroom mobility being accumulated preferably in the apical parts of the mushroom’s fruiting body (TF > 1). The highest mobility was demonstrated by Cd and Cu. Sodium was the only element with significantly low mobility (TF < 1), and it accumulated preferably in the stipe. Imleria badia seems to be sensitive to the accumulation of elements such as As, Cd, and Pb from the atmospheric deposits. Specific geochemistry of the growing substrate was reflected to different extend in the accumulation of elements such as Ag, Cu, Rb, S, Al, Ca, Fe, Ba, and Na in the mushroom’s fruiting bodies.

Sizeable net export of base cations from a Carpathian flysch catchment indicates their geogenic origin while the 26Mg/24Mg, 44Ca/40Ca and 87Sr/86Sr isotope ratios in runoff are indistinguishable from atmospheric input - Martin Novak; Yulia V. Erban Kochergina; Alexandre V. Andronikov; Chris Holmden; Frantisek Veselovsky; Vaclav Kachlik; Jakub Hruška; Frantisek Laufek; Tomas Paces; Arnost Komarek; Ondrej Sebek; Marketa Stepanova; et al. (Environmental Science and Pollution Research, 2024)
Nutrient imbalances may negatively affect the health status of forests exposed to multiple stress factors, including drought and bark beetle calamities. We studied the origin of base cations in runoff from a small Carpathian catchment underlain by base-poor flysch turbidites using magnesium (Mg), calcium (Ca) and strontium (Sr) isotope composition of 10 ecosystem compartments. Our objective was to constrain conclusions drawn from long-term hydrochemical monitoring of inputs and outputs. Annual export of Mg, Ca and Sr exceeds 5-to-15 times their atmospheric input. Mass budgets per se thus indicate sizeable net leaching of Mg, Ca and Sr from bedrock sandstones and claystones. Surprisingly, δ 26 Mg, δ 44 Ca and 87 Sr/ 86 Sr isotope ratios of runoff were practically identical to those of atmospheric deposition and soil water but significantly different from bedrock isotope ratios. We did not find any carbonates in the studied area as a hypothetical, easily dissolvable source of base cations whose isotope composition might corroborate the predominance of geogenic base cations in the runoff. Marine carbonates typically have lower δ 26 Mg and 87 Sr/ 86 Sr ratios, and silicate sediments often have higher δ 26 Mg and 87 Sr/ 86 Sr ratios than runoff at the study site. Mixing of these two sources, if confirmed, could reconcile the flux and isotope data.

Accumulation and within-mushroom distribution of elements in red cracking bolete (Xerocomellus chrysenteron) collected over the extended period from compositionally contrasting substrates - Alexandre V. Andronikov; Irina E. Andronikova; Ondrej Sebek; Eva Martinkova; Marketa Stepanova (Environmental Monitoring and Assessment, 2023)
We conducted a study of elemental compositions of Xerocomellus chrysenteron samples accompanied by samples of related substrate soils. All samples were collected during the harvesting seasons 2021 and 2022 from three forested sites almost unpolluted by recent human activities and underlain by contrasting bedrock (granite, amphibolite, and serpentinite). Elements such as Ag, Cd, K, P, Rb, S, Se, and Zn were the main elements enriched in the mushroom’s fruiting bodies relative to the substrate. Concentrations of most elements in mushrooms were not site-dependent, with only Ag, As, Rb, and Se concentrations significantly depending on the bedrock composition. Some elements analyzed in mushrooms displayed temporal features, but such features were not systematic and varied for each element. Most analyzed elements were distributed unevenly within the mushroom’s fruiting bodies, with apical parts generally enriched in mobile elements. Mushrooms influenced concentrations of Ag, Cd, K, and Rb and a few other elements in the substrate via uptake, but such influence was very limited and can be responsible for only 2.5–11.5% of total depletion of the affected substrate in the named elements.

Spatial and temporal trends in δ66Zn and 206Pb/207Pb isotope ratios along a rural transect downwind from the Upper Silesian industrial area: Role of legacy vs. present-day pollution - Eva Prechova; Ondrej Sebek; Martin Novak; Alexandre V. Andronikov; Ladislav Strnad; Vladislav Chrastny; Jerzy Cabala; Marketa Stepanova; Jan Pasava; Eva Martinkova; Petra Pacherova; Vladimir Blaha; et al. (Environmental Pollution, 2023)

Elemental and Cu–Zn isotopic compositions of two bolete mushrooms grown on contrasting substrates - Alexandre V. Andronikov; Irina E. Andronikova; Ondrej Sebek; Eva Martinkova; Marketa Stepanova; Hyacinta Vitkova; Elena Antalova (Applied Geochemistry, 2023)

Translocation of elements and fractionation of Mg, Cu, Zn, and Cd stable isotopes in a penny bun mushroom (Boletus edulis) from western Czech Republic - Alexandre V. Andronikov; Irina E. Andronikova; Eva Martinkova; Ondrej Sebek; Marketa Stepanova (Environmental Science and Pollution Research, 2023)
Boletus edulis mushroom behaved as an accumulating biosystem with respect to Ag, Rb, Zn, and K. The mushroom was not an efficient accumulator of toxic As, Pb, and Cr, but Se and Cd displayed much higher concentrations in the mushroom than in the substrate samples. Other elements were bioexclusive. Different elements had different within-mushroom mobilities. The highest mobilities were displayed by Zn and Ag, and the lowest by Ti. The mushroom’s fruiting body preferentially took up lighter Mg, Cu, and Cd isotopes (Δ 26 Mg FB-soil = −0.75‰; Δ 65 Cu FB-soil = −0.96‰; Δ 114 Cd FB-soil = −0.63‰), and the heavier 66 Zn isotope (Δ 66 Zn FB-soil = 0.92‰). Positive within-mushroom Zn isotope fractionation resulted in accumulation of the heavier 66 Zn (Δ 66 Zn cap-stipe = 0.12‰) in the mushroom’s upper parts. Cadmium displayed virtually no within-mushroom isotope fractionation. Different parts of the fruiting body fractionated Mg and Cu isotopes differently. The middle part of the stipe (3–6 cm) was strongly depleted in the heavier 26 Mg with respect to the 0–3 cm (Δ 26 Mg stipe(3–6)-stipe(0–3) = −0.73‰) and 6–9 cm (Δ 26 Mg stipe(6–9)-stipe(3–6) = 0.28‰) sections. The same stipe part was strongly enriched in the heavier 65 Cu with respect to the 0–3 cm (Δ 65 Cu stipe(3–6)-stipe(0–3) = 0.63‰) and 6–9 cm (Δ 65 Cu stipe(6–9)-stipe(3–6) = −0.42‰) sections. An overall tendency for the upper mushroom’s parts to accumulate heavier isotopes was noted for Mg (Δ 26 Mg cap-stipe = 0.20‰), Zn (Δ 66 Zn cap-stipe = 0.12‰), and Cd (Δ 114 Cd cap-stipe = 0.04‰), whereas Cu showed the opposite trend (Δ 65 Cu cap-stipe = −0.08‰).

Temporal Changes in Mountain Slope Gradients in the Concentrations of Pollutants and Pb Isotope Ratios Near the Ostrava Conurbation (Upper Silesia, Czech-Polish Border) - Eva Prechova; Ondrej Sebek; Ladislav Strnad; Martin Novak; Vladislav Chrastny; Marketa Stepanova; Jan Pasava; Frantisek Veselovsky; Jan Curik; Petra Pacherova; Leona Bohdalkova; Marie Houskova (Water, Air, & Soil Pollution, 2020)

Retraction Statement: Comparison of nitrogen inputs and accumulation in 210 Pb‐dated peat cores: Evidence for biological N 2 ‐fixation in Central European peatlands despite decades of atmospheric N pollution - Martin Novak; Melanie A. Vile; Jan Curik; Bohuslava Cejkova; Jiri Barta; Marketa Stepanova; Ivana Jackova; Frantisek Buzek; Leona Bohdalkova; Eva Prechova; Frantisek Veselovsky; Marie Adamova; et al. (Global Change Biology, 2019)
“Comparison of nitrogen inputs and accumulation in 210 Pb‐dated peat cores: Evidence for biological N 2 ‐fixation in Central European peatlands despite decades of atmospheric N pollution” https://doi.org/10.1111/gcb.14505 , by Martin Novak, Melanie A. Vile, Jan Curik, Bohuslava Cejkova, Jiri Barta, Marketa Stepanova, Ivana Jackova, Frantisek Buzek, Leona Bohdalkova, Eva Prechova, Frantisek Veselovsky, Marie Adamova, Ivana Valkova and Arnost Komarek . The above article, first published online in Wiley Online Library (wileyonlinelibrary.com) in Global Change Biology, has been retracted by agreement between the authors, the journal Editor‐in‐Chief, Stephen P. Long, and John Wiley & Sons Ltd. Since publication of the above article, it was brought to the attention of the authors that the peat accretion rates violate reasonable ranges of peatland C/N/P stoichiometry, placing the quantitative conclusions of the article in serious error. The authors apologize for any inconvenience the publication of this work may have caused our readers. REFERENCE Novak, M., Vile, M. A., Cejkova, B., Barta, J., Stepanova, M., Jackova, I., Buzek, F., Bohdalkova, L., Prechova, E., Veselovsky, F., Adamova, M., Valkova, I., & Komarek, A. (2018). Comparison of nitrogen inputs and accumulation in 210 Pb‐dated peat cores: Evidence for biological N 2 ‐fixation in Central European peatlands despite decades of atmospheric N pollution. Global Change Biology .. https://doi.org/10.1111/gcb.14505

The Fate of 15N Tracer in Waterlogged Peat Cores from Two Central European Bogs with Different N Pollution History - Martin Novak; Marketa Stepanova; Frantisek Buzek; Ivana Jackova; Jan Curik; Frantisek Veselovsky; Eva Prechova; Elena Antalova; Jarmila Brychnacova; Ivana Bufkova; Arnost Komarek (Water, Air, & Soil Pollution, 2018)

Contrasting δ15N Values of Atmospheric Deposition and Sphagnum Peat Bogs: N Fixation as a Possible Cause - Martin Novak; Ivana Jackova; Jan Curik; Marketa Stepanova; Frantisek Veselovsky; Frantisek Buzek; Melanie A. Vile; Ivana Bufkova; Ivana Valkova; Marie Adamova; Leona Bohdalkova; Arnost Komarek (Ecosystems, 2016)